Enhanced modified granite stone powder-based road base material and preparation method thereof

By introducing temperature-responsive nanofiber hydrogel and kebab fiber-cotton fiber blended fabric/epoxy resin composite long fibers into the road base material, the problems of unevenness and cracks in the existing materials during construction are solved, and the materials are realized High water stability and durability reduce production costs and environmental impacts.

CN119430811APending Publication Date: 2025-02-14WUHAN METALLURGY ARCHITECTURE RES YUAN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411809193.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing road base materials have unevenness during construction, which are prone to thermal stress cracks and dry shrink cracks, and lack effective moisture retention and temperature adjustment solutions, which affect the durability and environmental performance of the material.

Method used

Using reinforced modified granite stone powder-based materials, the construction uniformity and crack resistance of the material are improved by introducing temperature-responsive nanofiber hydrogel and kebab fiber-cotton fiber blended fabric/epoxy resin composite long fibers, and through nano The temperature responsiveness of the fiber hydrogel regulates the temperature during cement hydration.

Benefits of technology

It effectively improves the construction uniformity and integrity of road base materials, prevents the occurrence of thermal stress and dry shrinkage cracks, improves the durability and water stability of the materials, and reduces production costs and environmental impacts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005180107560000061
    Figure BDA0005180107560000061
  • Figure BDA0005180107560000071
    Figure BDA0005180107560000071
Patent Text Reader

Abstract

The invention discloses an enhanced modified granite stone powder-based road base material and a preparation method thereof, and the road base material comprises the following raw materials by mass: 100 parts of waste granite stone powder, 3-8 parts of cement, 0.5-1 part of a multifunctional water stabilizer, and 1-5 parts of temperature-responsive nanofiber hydrogel. 0.5-2 parts of kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber, and 8-13 parts of water. According to the method disclosed by the invention, by introducing the temperature-responsive nanofiber hydrogel and the kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber, the modified material capable of improving the construction uniformity and integrity of the road base material and effectively preventing thermal stress cracks and shrinkage cracks is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a reinforced modified granite powder-based road base material and a preparation method thereof. Background Art

[0002] In the field of road construction, the selection of base materials plays a vital role in the stability and durability of roads. In recent years, with the increasing awareness of environmental protection and resource recycling, waste granite powder has been gradually explored as a potential building material for road base materials. However, in the actual application process, there are some technical difficulties and shortcomings, which urgently need to be improved and optimized.

[0003] Problems encountered when using granite powder as a road base material: 1. Uneven construction: Due to its fine particle size and large specific surface area, granite powder is prone to uneven construction during the mixing process, affecting the density and integrity of the road base; 2. Thermal stress cracks: Not only are they caused by the exothermic reaction during cement hydration, but they may also be caused by the thermal expansion and contraction effect caused by changes in ambient temperature. The heat released during cement hydration, especially when constructed under high temperature conditions, may cause local overheating, which in turn causes thermal stress cracks. At the same time, periodic changes in temperature can also cause slight changes in the volume of the material. This repeated thermal expansion and contraction may also cause cracks in the road base material; 3. Shrinkage cracks: During the construction and use of the road base, especially under drought or high temperature conditions, the rapid loss of water can lead to shrinkage cracks.

[0004] The existing road base material technology usually adopts the following methods when trying to solve the above problems: 1. Adjust the material ratio: By changing the ratio of cement, stone powder and other additives, the stability and durability of the material are improved; 2. Use traditional additives: Introduce traditional additives to improve material performance, but these additives often have a single function and cannot fully solve the problems of thermal stress and shrinkage; 3. Improve the construction process: Reduce the occurrence of cracks by improving the construction process, but this method often increases the construction cost and complexity. Although these methods have improved the performance of road base materials to a certain extent, they still have the following shortcomings: lack of a comprehensive solution for effectively regulating cement hydration heat release and water retention. In addition, the existing road base materials also have problems in water absorption. When the ambient humidity is low, the material cannot effectively replenish the ambient moisture, and when the ambient humidity is too high, the material cannot effectively absorb moisture, resulting in unstable material performance; failed to fully utilize the potential of waste materials and improve the recycling rate of resources; high construction costs, and limitations in environmental protection and sustainable development. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide an enhanced modified granite powder-based road base material and a preparation method in view of the shortcomings of the prior art. The method introduces temperature-responsive nanofiber hydrogel and kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fibers to prepare a modified material that improves the construction uniformity and integrity of the road base material and effectively prevents thermal stress cracks and shrinkage cracks.

[0006] The technical solution adopted by the present invention to solve the above-mentioned problems is:

[0007] A reinforced modified granite powder-based road base material comprises the following raw materials in parts by mass: 100 parts of waste granite powder, 3-8 parts of cement, 0.5-1 part of a multifunctional water stabilizer, 1-5 parts of a temperature-responsive nanofiber hydrogel, 0.5-2 parts of a kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber, and 8-13 parts of water.

[0008] In the above scheme, the method for preparing the temperature-responsive nanofiber hydrogel comprises the following steps:

[0009] In a container equipped with a stirrer, a temperature control system and a dripping device, 60 parts by mass of N-isopropylacrylamide and 24-36 parts by mass of deionized water are mixed and heated to 70-80° C., and 0.5-1 parts by mass of an initiator is added and dissolved under nitrogen protection;

[0010] A mixed monomer solution consisting of 50-70 parts by mass of N-isopropylacrylamide, 5-10 parts by mass of acrylic acid, 1-3 parts by mass of a cross-linking agent and 5-10 parts by mass of a temperature-responsive functional agent is added dropwise, and the reaction temperature is maintained at 70-80°C and stirred for 4-6 hours; after the reaction is completed, the product is cooled to room temperature, filtered and washed, and dried at room temperature to obtain a temperature-responsive nanofiber hydrogel.

[0011] In the above scheme, the temperature responsive functional agent is a mixture of glycidyl methacrylate and a surface group modifier, and the mass ratio of the glycidyl methacrylate to the surface group modifier is 1:1-1:3;

[0012] The preparation method of the surface group modifier is as follows: amino silicone oil, hydroxy short-chain alkyl alkenyl silicone oil and fatty alcohol polyoxyethylene ether are added into anhydrous ethanol in a mass ratio of (1-3):3:(1-3), heated to 75-90°C under stirring for reaction for 1.5-3.5 hours, and filtered after the reaction to obtain the surface group modifier.

[0013] In the above scheme, the initiator is one of ammonium persulfate, hydrogen peroxide, benzoyl peroxide, diethyl peroxide, and azobisisobutyronitrile.

[0014] In the above scheme, the cross-linking agent is one of N,N'-methylenebisacrylamide, acrylamide, N,N'-bisacrylamide, and ethylene glycol diacrylate.

[0015] In the above scheme, the method for preparing the kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber comprises the following steps:

[0016] Pre-treating 50-70 parts by weight of kenaf fibers and 30-50 parts by weight of cotton fibers and mixing them to form a blended fabric;

[0017] Mix 50-100 parts by mass of a hydrophilic modified epoxy resin and 5-10 parts by mass of a curing agent, and add 0.5-1.0 parts by mass of an accelerator to adjust the reaction speed to form an epoxy resin mixture;

[0018] The blended fabric is immersed in the epoxy resin mixture to ensure that the fibers are fully impregnated, and a curing reaction is carried out at a temperature of 20-80° C. After the reaction is completed, the kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber is obtained.

[0019] In the above scheme, the hydrophilic modified epoxy resin is one of hydrophilic modified bisphenol A type epoxy resin, epoxybutylene glycol resin, and bisaminophenol type epoxy resin.

[0020] In the above scheme, the curing agent is one of methyltetrahydrobenzoquinone, isocyanate curing agent, aromatic amine curing agent and epoxyglutaric acid ester curing agent.

[0021] In the above scheme, the accelerator is one of diethylamine benzenesulfonate, citric acid and phenol.

[0022] In the above scheme, the pretreatment includes cleaning, degreasing and drying to ensure that the fiber surface is clean.

[0023] In the above scheme, the waste granite powder is used as the main aggregate and has a moisture content of no more than 13%.

[0024] In the above scheme, the cement used as the cementitious material is ordinary Portland cement with a specification of P·O42.5 and above.

[0025] In the above scheme, the preparation method of the multifunctional water stabilizer refers to patent CN117700174A, and includes the following steps: preparing a mixed solution of acrylic monomers, adding an aqueous solution of nanosol under stirring, stirring and mixing for 20-40 minutes; heating to 80°C-90°C, adding an aqueous solution of ammonium persulfate, reacting for 1-2 hours, and obtaining a multifunctional water stabilizer. The acrylic monomers are calculated by weight: 5-7 parts of methyl methacrylate, 26-28 parts of butyl acrylate, 0.5-0.9 parts of glycidyl methacrylate, and 0.1-0.5 parts of acrylic acid. The nanosol is one of nano silica sol and nano aluminum sol or a mixture of the two, with a particle size of 10-35nm; the amount used is 30%-40% of the total mass of the acrylic monomers. The amount of ammonium persulfate used is 0.5%-2% of the total mass of the acrylic monomers.

[0026] The present invention also provides a method for preparing a reinforced modified granite powder-based road base material, comprising the following steps:

[0027] The waste granite powder, cement, multifunctional water stabilizer, temperature-responsive nanofiber hydrogel, kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber and water are uniformly mixed to obtain a mixture;

[0028] The obtained mixture is compacted with a compaction degree of 95% to 100% to obtain the enhanced modified granite powder-based road base material.

[0029] In the above scheme, the temperature-responsive nanofiber hydrogel needs to absorb water to reach a saturated state before use; when the ambient temperature of the hydrogel increases, its surface structure changes from hydrophobic groups to hydrophilic groups, resulting in the release of internal water, which helps to control heat and regulate moisture.

[0030] In the above scheme, the water absorption rate of the kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber needs to be maintained at 60% to 75% of the saturated water absorption rate before use; the composite long fiber can replenish moisture to the environment through the humidity gradient when the ambient humidity is low, and can also absorb moisture when the ambient humidity is too high, thereby improving the crack resistance and durability of the material.

[0031] In the present invention, temperature-responsive nanofiber hydrogel is innovatively applied. This material can change its hydrophilicity at a specific temperature. This change is achieved through the temperature-sensitive functional groups contained in the hydrogel. These functional groups change their hydrophilicity / hydrophobicity properties under temperature changes. When the temperature exceeds 35°C, the surface structure of the hydrogel changes from hydrophilic to hydrophobic. In this way, during the exothermic process of cement hydration, the hydrogel can absorb and release water, adjust the temperature during cement hydration, prevent local overheating, and thus control the generation of thermal stress cracks. At the same time, the present invention also innovatively applies kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fibers, and introduces long fiber materials formed by kenaf fiber and cotton fiber composited with epoxy resin. These composite long fibers have high water absorption in the saturated water absorption state, while maintaining high mechanical strength. The composite long fibers prepared through blending technology and epoxy resin impregnation and curing process not only improve the crack resistance of road base materials, but also enhance the integrity and durability of the materials by forming a moisture channel network. This combination utilizes the renewability of natural fibers and the high mechanical properties of epoxy resin, providing a new type of reinforcement material while preventing shrinkage cracks caused by rapid loss of moisture in road base materials.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The enhanced modified granite powder-based road base material prepared by the present invention not only has high water stability, but also effectively improves the construction uniformity and integrity of the material through the application of temperature-responsive nanofiber hydrogel and kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber, prevents the occurrence of thermal stress cracks and shrinkage cracks, and improves the durability of the road base.

[0034] (2) The preparation method of the present invention achieves a reduction in material cost and environmental impact by using waste granite powder and composite long fibers, reflecting the dual optimization of environmental protection and economy. The reuse of waste granite powder reduces the demand for new stone and reduces the problem of waste disposal; in addition, the use of composite long fibers not only improves material performance, but also enhances the environmental attributes of the material due to its renewability. The overall solution reduces production costs and reduces environmental impact, has significant economic and social benefits, and meets the requirements of sustainable development. DETAILED DESCRIPTION

[0035] The technical solution of the present invention will be fully and clearly described below in conjunction with specific embodiments, but the described embodiments are only some embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0036] The present application provides a reinforced modified granite powder-based road base material, comprising the following raw materials in parts by mass: 100 parts of waste granite powder, 3-8 parts of cement, 0.5-1 part of multifunctional water stabilizer, 1-5 parts of temperature-responsive nanofiber hydrogel, 0.5-2 parts of kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber, and 8-13 parts of water; wherein the cement used is ordinary Portland cement with a specification of P·O42.5 and above; and the moisture content of the waste granite powder is not more than 13%.

[0037] The method for preparing the temperature-responsive nanofiber hydrogel comprises the following steps:

[0038] In a container equipped with a stirrer, a temperature control system and a dripping device, 60 parts by mass of N-isopropylacrylamide and 36 parts by mass of deionized water are mixed and heated to 80° C., and 1 part by mass of initiator ammonium persulfate is added and dissolved under nitrogen protection;

[0039] A mixed monomer solution consisting of 70 parts by mass of N-isopropyl acrylamide, 10 parts by mass of acrylic acid, 3 parts by mass of a crosslinking agent N,N'-methylenebisacrylamide and 10 parts by mass of a temperature-responsive functional agent is added dropwise, and the reaction temperature is maintained at 80°C for continuous stirring for 6 hours; after the reaction is completed, the product is cooled to room temperature, filtered and washed, and dried at room temperature to obtain a temperature-responsive nanofiber hydrogel. The temperature-responsive functional agent is a mixture of 12 parts by mass of glycidyl methacrylate and 36 parts by mass of a surface group modifier; the specific preparation method of the surface group modifier is as follows: amino silicone oil, hydroxyl short-chain alkyl alkenyl silicone oil, and fatty alcohol polyoxyethylene ether are added to 20 parts by mass of anhydrous ethanol in a mass ratio of 1:2:1 (5 parts by mass of amino silicone oil), heated to 80°C for reaction for 2 hours under stirring, and filtered to obtain a surface group modifier after the reaction is completed. The temperature-responsive nanofiber hydrogel prepared by the present invention changes from hydrophilic to hydrophobic when it exceeds 35°C.

[0040] The preparation method of the above-mentioned kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber comprises the following steps:

[0041] 50 parts by weight of kenaf fibers and 35 parts by weight of cotton fibers are pretreated and mixed to form a blended fabric;

[0042] 75 parts by mass of a hydrophilic modified bisphenol A epoxy resin and 6 parts by mass of a curing agent, methyltetrahydrobenzoquinone, were mixed, and 1.0 parts by mass of an accelerator, diethylamine benzenesulfonate, was added to adjust the reaction rate to form an epoxy resin mixture;

[0043] The blended fabric is immersed in the epoxy resin mixture to ensure that the fibers are fully impregnated, and a curing reaction is carried out at a temperature of 80° C. After the reaction is completed, the product is post-treated to obtain the kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber.

[0044] The preparation method of the multifunctional water stabilizer is based on patent CN117700174A.

[0045] Example 1

[0046] The preparation method of the enhanced modified granite powder-based road base material comprises the following steps:

[0047] 100 parts by mass of waste granite powder, 5 parts by mass of cement, 1 part by mass of multifunctional water stabilizer, 5 parts by mass of temperature-responsive nanofiber hydrogel, 1.5 parts by mass of kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber and 8 parts by mass of water are uniformly mixed to obtain a mixture; wherein the temperature-responsive nanofiber hydrogel needs to absorb water to reach a saturated state before use, and the kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber needs to maintain a water absorption rate of 75% of the saturated water absorption rate before use.

[0048] The obtained mixture is compacted with a compaction degree of 95% to obtain a reinforced modified granite powder-based road base material.

[0049] Example 2

[0050] The preparation method of the enhanced modified granite powder-based road base material comprises the following steps:

[0051] 100 parts by mass of waste granite powder, 7 parts by mass of cement, 1 part by mass of multifunctional water stabilizer, 4 parts by mass of temperature-responsive nanofiber hydrogel, 1.5 parts by mass of kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber and 8 parts by mass of water are uniformly mixed to obtain a mixture; wherein the temperature-responsive nanofiber hydrogel needs to absorb water to reach a saturated state before use, and the kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber needs to maintain a water absorption rate of 75% of the saturated water absorption rate before use.

[0052] The obtained mixture is compacted with a compaction degree of 95% to obtain a reinforced modified granite powder-based road base material.

[0053] Example 3

[0054] The preparation method of the enhanced modified granite powder-based road base material comprises the following steps:

[0055] 100 parts by mass of waste granite powder, 8 parts by mass of cement, 1 part by mass of a multifunctional water stabilizer, 2 parts by mass of temperature-responsive nanofiber hydrogel, 1 part by mass of kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fibers and 8 parts by mass of water are uniformly mixed to obtain a mixture; wherein the temperature-responsive nanofiber hydrogel needs to absorb water to reach a saturated state before use, and the kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fibers need to maintain a water absorption rate of 60% of the saturated water absorption rate before use.

[0056] The obtained mixture is compacted with a compaction degree of 98% to obtain a reinforced modified granite powder-based road base material.

[0057] Comparative Example 1

[0058] The method for preparing a granite powder-based road base material comprises the following steps:

[0059] 100 parts by mass of waste granite powder, 5 parts by mass of cement, 0.5 parts by mass of multifunctional water stabilizer and 8 parts by mass of water are uniformly mixed to obtain a mixture; the obtained mixture is compacted with a compaction degree of 98% to obtain a granite powder-based road base material.

[0060] Comparative Example 2

[0061] The method for preparing a granite powder-based road base material comprises the following steps:

[0062] 100 parts by mass of waste granite powder, 5 parts by mass of cement, 0.5 parts by mass of a multifunctional water stabilizer, 2 parts by mass of kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fibers and 8 parts by mass of water are uniformly mixed to obtain a mixture; the obtained mixture is compacted with a compaction degree of 98% to obtain a granite powder-based road base material; wherein the kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fibers need to maintain a water absorption rate of 75% of the saturated water absorption rate before use.

[0063] Comparative Example 3

[0064] The method for preparing a granite powder-based road base material comprises the following steps:

[0065] 100 parts by mass of waste granite powder, 5 parts by mass of cement, 0.5 parts by mass of multifunctional water stabilizer, 5 parts by mass of temperature-responsive nanofiber hydrogel and 8 parts by mass of water are uniformly mixed to obtain a mixture; the obtained mixture is compacted with a compaction degree of 98% to obtain a granite powder-based road base material; wherein the temperature-responsive nanofiber hydrogel needs to absorb water to reach a saturated state before use.

[0066] The enhanced modified granite powder-based road base materials prepared in Examples 1-3 and the granite powder-based road base materials prepared in Comparative Examples 1-3 were tested and analyzed by on-site core sampling (in order to reflect its uniformity, 5 groups of core results were taken in each test section and the variance was analyzed) for their 7-day unconfined compressive strength, the percentage of strength loss after 7 days of soaking in water, and the percentage of crack area. The results are shown in the following table; the water stability of the test block is expressed by the percentage of strength loss after 7 days of soaking in water (%), and the strength of the test block under standard curing conditions and the strength of the test block under 7 days of soaking in water are tested, subtracted and divided by the strength of the test block under standard curing conditions to obtain the percentage of strength loss after 7 days of soaking in water for water stability (%); the crack area percentage is obtained by taking a panoramic view of the surface with a high-definition camera, and analyzing the crack area ratio by img Pro Plus software to obtain the crack area percentage.

[0067] Test results of different examples and comparative examples

[0068]

[0069]

[0070] Through the above embodiments, the present invention not only provides a modified granite powder-based road base material with high water stability, good construction uniformity and integrity, but also demonstrates a method for optimizing material properties by adjusting the raw material ratio and process parameters. These embodiments fully demonstrate the flexibility and adaptability of the present invention, which can be adjusted and optimized according to different application requirements.

[0071] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An enhanced modified granite powder-based road base material, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of waste granite powder, 3-8 parts of cement, 0.5-1 parts of multifunctional water stabilizer, 1-5 parts of temperature-responsive nanofiber hydrogel, 0.5-2 parts of kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber, and 8-13 parts of water.

2. The enhanced modified granite powder-based road base material according to claim 1, characterized in that: The method for preparing the temperature-responsive nanofiber hydrogel comprises the following steps: Mix 60 parts by mass of N-isopropylacrylamide and 24-36 parts by mass of deionized water, heat to 70-80° C., add 0.5-1 parts by mass of initiator under nitrogen protection and dissolve; A mixed monomer solution consisting of 50-70 parts by mass of N-isopropylacrylamide, 5-10 parts by mass of acrylic acid, 1-3 parts by mass of a cross-linking agent and 5-10 parts by mass of a temperature-responsive functional agent is added dropwise, and the reaction temperature is maintained at 70-80°C and stirred for 4-6 hours; after the reaction is completed, the product is cooled to room temperature, filtered and washed, and dried at room temperature to obtain a temperature-responsive nanofiber hydrogel.

3. The enhanced modified granite powder-based road base material according to claim 2, characterized in that: The temperature responsive functional agent is a mixture of glycidyl methacrylate and a surface group modifier, and the mass ratio of the glycidyl methacrylate to the surface group modifier is 1:1-1:3; The preparation method of the surface group modifier is as follows: amino silicone oil, hydroxy short-chain alkyl alkenyl silicone oil and fatty alcohol polyoxyethylene ether are added into anhydrous ethanol in a mass ratio of (1-3):3:(1-3), heated to 75-90°C under stirring for reaction for 1.5-3.5 hours, and filtered after the reaction to obtain the surface group modifier.

4. The enhanced modified granite powder-based road base material according to claim 2, characterized in that: The initiator is one of ammonium persulfate, hydrogen peroxide, benzoyl peroxide, diethyl peroxide, and azobisisobutyronitrile; the crosslinking agent is one of N,N'-methylenebisacrylamide, acrylic acid amide, N,N'-bisacrylamide, and ethylene glycol diacrylate.

5. The enhanced modified granite powder-based road base material according to claim 1, characterized in that: The preparation method of the kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber comprises the following steps: Pre-treating 50-70 parts by weight of kenaf fibers and 30-50 parts by weight of cotton fibers and mixing them to form a blended fabric; Mix 50-100 parts by mass of a hydrophilic modified epoxy resin and 5-10 parts by mass of a curing agent, and add 0.5-1.0 parts by mass of an accelerator to form an epoxy resin mixture; The blended fabric is impregnated in the epoxy resin mixture, and a curing reaction is performed at a temperature of 20-80° C. After the reaction is completed, the kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber is obtained; The hydrophilic modified epoxy resin is one of hydrophilic modified bisphenol A epoxy resin, epoxy butanediol resin, and bisamine phenol epoxy resin; the curing agent is one of methyl tetrahydrobenzoquinone, isocyanate curing agent, aromatic amine curing agent, and epoxy glutaric ester curing agent; the accelerator is one of diethylamine benzenesulfonate, citric acid, and phenol.

6. The enhanced modified granite powder-based road base material according to claim 5, characterized in that: The pretreatment includes cleaning, degreasing and drying.

7. The enhanced modified granite powder-based road base material according to claim 1, characterized in that: The water content of the waste granite powder is no more than 13%.

8. The enhanced modified granite powder-based road base material according to claim 1, characterized in that: The cement is ordinary Portland cement with a specification of P·O42.5 and above; The multifunctional water stabilizer is prepared by reacting a mixed solution of acrylic monomers, an aqueous solution of nano-sol and an aqueous solution of ammonium sulfate.

9. The method for preparing the enhanced modified granite powder-based road base material according to claim 1, characterized in that: The following steps are involved: The waste granite powder, cement, multifunctional water stabilizer, temperature-responsive nanofiber hydrogel, kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber and water are uniformly mixed to obtain a mixture; The obtained mixture is compacted with a compaction degree of 95% to 100% to obtain the enhanced modified granite powder-based road base material.

10. The method for preparing the enhanced modified granite powder-based road base material according to claim 9, characterized in that: The temperature-responsive nanofiber hydrogel needs to absorb water to reach a saturated state before use; the kenaf fiber-cotton fiber blended fabric / epoxy resin composite long fiber needs to maintain a water absorption rate of 60% to 75% of the saturated water absorption rate before use.